# Solve for t 16t^2+3t-54=0 16t2+3t-54=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=16, b=3, and c=-54 into the quadratic formula and solve for t.
-3±32-4⋅(16⋅-54)2⋅16
Simplify.
Simplify the numerator.
Raise 3 to the power of 2.
t=-3±9-4⋅(16⋅-54)2⋅16
Multiply 16 by -54.
t=-3±9-4⋅-8642⋅16
Multiply -4 by -864.
t=-3±9+34562⋅16
Add 9 and 3456.
t=-3±34652⋅16
Rewrite 3465 as 32⋅385.
Factor 9 out of 3465.
t=-3±9(385)2⋅16
Rewrite 9 as 32.
t=-3±32⋅3852⋅16
t=-3±32⋅3852⋅16
Pull terms out from under the radical.
t=-3±33852⋅16
t=-3±33852⋅16
Multiply 2 by 16.
t=-3±338532
t=-3±338532
The final answer is the combination of both solutions.
t=-3-338532,-3+338532
The result can be shown in multiple forms.
Exact Form:
t=-3-338532,-3+338532
Decimal Form:
t=1.74575783…,-1.93325783…
Solve for t 16t^2+3t-54=0

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top